1968
DOI: 10.1002/j.1551-8833.1968.tb03614.x
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Trace Metals by Foam Separation Processes

Abstract: This article describes research on the use of foam separation processes for removing metal ions from water. Whether the removal process is a foam fractionation, precipitate flotation, or ion flotation depends primarily on the nature of the metal‐collector product, the sublate. Factors affecting the solubility of the sublate, and therefore the mechanism, include the coordination behavior of the metal toward the collector surfactant, the nature of the collector, and the pH of the solution. Other variables that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1968
1968
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Studies of flotation kinetics are useful in elucidating the mechanism of the process and serve as predictive tools in the implementation of flotation technology. Chemical kinetics principles have been used in the modeling of flotation processes, particularly in the formulation of the basic rate equation. , Studies of the kinetics of ion flotation have been carried out by different investigators, and the process has been shown to follow the first-order equation k = prefix− c normali c normalr c normali t nobreak0em0.25em⁡ ln nobreak0em.25em⁡ c c normalr c normali c normalr where k is the kinetic rate constant; t is the flotation time; and c i , c r , and c are the initial, residual, and time-dependent ion concentrations in solution, respectively. The rate constant, k , can be estimated by a correct data fitting of c values against flotation time.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of flotation kinetics are useful in elucidating the mechanism of the process and serve as predictive tools in the implementation of flotation technology. Chemical kinetics principles have been used in the modeling of flotation processes, particularly in the formulation of the basic rate equation. , Studies of the kinetics of ion flotation have been carried out by different investigators, and the process has been shown to follow the first-order equation k = prefix− c normali c normalr c normali t nobreak0em0.25em⁡ ln nobreak0em.25em⁡ c c normalr c normali c normalr where k is the kinetic rate constant; t is the flotation time; and c i , c r , and c are the initial, residual, and time-dependent ion concentrations in solution, respectively. The rate constant, k , can be estimated by a correct data fitting of c values against flotation time.…”
Section: Resultsmentioning
confidence: 99%
“…With appropriate collectors, concentration by ion flotation of the fluorozirconate ion (777) and the ions of europium, cesium, and strontium has been reported and compared favorably with flocculation (77). The batch removal rates of lead, iron, and copper have been studied (115).…”
Section: Recently Reported Adsubble Separationsmentioning
confidence: 99%
“…(1) to investigate the micro flotation of Bacillus cereus, which is larger and more hydrophobic than the other bacteria studied; (2) to determine the effect of coagulant concentration on the pH range of efficient microflotation; and (3) to examine the relative effectiveness of soluble and insoluble cationic and anionic collectors.…”
Section: Collectors and Frothersmentioning
confidence: 99%